2021
DOI: 10.1186/s12909-021-02908-0
|View full text |Cite
|
Sign up to set email alerts
|

‘The best interest of patients, not self-interest’: how clinicians understand altruism

Abstract: Background Altruism refers to acting in ‘the best interest of patients, not self-interest’. With an observed discordance between the concept and practice of altruism, and increasing attention to ‘pathologic altruism’, the role of altruism is blurred in present day medical care. In this background, the required balance of altruistic attitude which needs to be fostered in medical students needs clarity. This problem may be best addressed by the practicing clinicians. The objectives of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Other studies have also found that cultural attitudes about health professionals, and individual professional identities play a role in MJH(Humphrey and Russell 2004;Moghri et al 2022). Although the role of altruism has been described in improving commitment of health workers to their work(Sajjad et al 2021), others have pointed to the reality of meeting family obligations(Lo et al 2018). The study participants highlighted the need to support or meet the expectations of extended family as one of the drivers of MJH.…”
mentioning
confidence: 99%
“…Other studies have also found that cultural attitudes about health professionals, and individual professional identities play a role in MJH(Humphrey and Russell 2004;Moghri et al 2022). Although the role of altruism has been described in improving commitment of health workers to their work(Sajjad et al 2021), others have pointed to the reality of meeting family obligations(Lo et al 2018). The study participants highlighted the need to support or meet the expectations of extended family as one of the drivers of MJH.…”
mentioning
confidence: 99%
“…Rather, a more realistic approach to practice altruism requires prioritizing patients' interest but also identifying one's individual capacity and making a conscious effort to balance work-life commitments in this regard. Such a balanced altruistic approach may be more effective and sustainable in the long run (Sajjad et al, 2021).…”
mentioning
confidence: 99%
“…This may also include substituting an alternative treatment for patients who can't afford a certain treatment rather than denying it altogether. Promoting a workplace altruistic culture with organized team efforts for altruistic activities based on a commitment to prioritize patients' interest at all times is desirable (Sajjad et al, 2021). This may include activities like generating ward funds for needy patients and having a system of backups in situations where doctors have a personal or family emergency or commitment.…”
mentioning
confidence: 99%